2006
DOI: 10.1086/501367
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Increase in Fitness Cost with Increased β‐Lactam Resistance in Pneumococci Evaluated by Competition in an Infant Rat Nasal Colonization Model

Abstract: The cost of penicillin-resistance acquisition for the Streptococcus pneumoniae strain competing with its susceptible ancestor to colonize the URT increases with the number of resistant pbp alleles acquired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 35 publications
3
54
1
Order By: Relevance
“…Third, we constrained our parameter sets to a set of scenarios with very low fitness costs, to ensure that it was possible for high-level resistance to spread. Although there are no quantitative estimates of fitness costs for fluoroquinolone resistance, it seems possible that the costs are higher than the values considered here (36,37), meaning that the actual probability for using newer fluoroquinolones without exten- Typical and atypical results are presented as mean (SD). *Typical results of highest Resistance occur with immediate switch, whereas atypical results occur with delayed switch.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Third, we constrained our parameter sets to a set of scenarios with very low fitness costs, to ensure that it was possible for high-level resistance to spread. Although there are no quantitative estimates of fitness costs for fluoroquinolone resistance, it seems possible that the costs are higher than the values considered here (36,37), meaning that the actual probability for using newer fluoroquinolones without exten- Typical and atypical results are presented as mean (SD). *Typical results of highest Resistance occur with immediate switch, whereas atypical results occur with delayed switch.…”
Section: Discussionmentioning
confidence: 97%
“…The wide clonal spread of highly resistant strains (33) suggests that these strains are not much compromised in their fitness and are capable of spreading. The existence of fit, highly resistant strains may imply compensatory chromosomal changes (34,35), because animal studies showed pneumococcal strains as being greatly compromised in vivo upon acquisition of high-level resistant alleles (36,37). These characteristics suggest that, in the case of amoxicillin, the policy that maximizes treatment success (widespread use of higher doses) may unfortunately foster the emergence of higher-level resistance at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…tudies of within-host competition between bacteria typically measure selection by the mean change in the logarithm of the ratio of a favored to a disfavored allele (1)(2)(3)(4), sometimes called a "competitive index." In animal experiments, there is often substantial variation in the competition outcome among animal subjects (1)(2)(3)(4), which necessitates the use of a large number of animals to ensure reproducible results (5).…”
mentioning
confidence: 99%
“…In animal experiments, there is often substantial variation in the competition outcome among animal subjects (1)(2)(3)(4), which necessitates the use of a large number of animals to ensure reproducible results (5). Understanding the source of this variation is important for a number of purposes, including sample size calculations in experimental design and results interpretation.…”
mentioning
confidence: 99%
“…Specifically, a fitness loss accompanied antibiotic resistance due to mutation of the target gene in animal models of Staphylococcus aureus (129), Salmonella enterica serovar Typhimurium (20,111), and Streptococcus pneumoniae (189) infection. An exception to these studies is the reported colonization advantage displayed by some fluoroquinolone-resistant Campylobacter jejuni strains due to mutation of gyrB (108).…”
Section: Discussionmentioning
confidence: 99%